Encyclopedia of Inorganic and Bioinorganic Chemistry 2004
DOI: 10.1002/9781119951438.eibc0566
|View full text |Cite
|
Sign up to set email alerts
|

Ferredoxins Containing One [3Fe–4S] Cluster.Desulfovibrio GigasFerredoxinII– Solution Structure

Abstract: Functional Class Occurrence Biological Function Amino Acid Sequence Information Protein Production, Purification and Molecular Characterization Metal Content and Cluster Type Spectroscopy NMR Solution Structure of Native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…The protein presents two discernible absorption bands in the 300 -500-nm region with maxima at ϳ340 and 420 nm, respectively, as well as a broad shoulder in the 500 -600-nm region. The shape and location of these bands are typical of broad ligand-to-metal charge transfer in iron-sulfur proteins such as ferredoxins (29,30) and indicated that iron-sulfur clusters had been successfully incorporated into f-HupS. This is further substantiated by the 420/315 nm absorbance ratio of 0.43, which is comparable with the corresponding ratio 0.68 found in ferredoxin II from Desulfovibrio gigas (29).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The protein presents two discernible absorption bands in the 300 -500-nm region with maxima at ϳ340 and 420 nm, respectively, as well as a broad shoulder in the 500 -600-nm region. The shape and location of these bands are typical of broad ligand-to-metal charge transfer in iron-sulfur proteins such as ferredoxins (29,30) and indicated that iron-sulfur clusters had been successfully incorporated into f-HupS. This is further substantiated by the 420/315 nm absorbance ratio of 0.43, which is comparable with the corresponding ratio 0.68 found in ferredoxin II from Desulfovibrio gigas (29).…”
Section: Resultssupporting
confidence: 59%
“…The shape and location of these bands are typical of broad ligand-to-metal charge transfer in iron-sulfur proteins such as ferredoxins (29,30) and indicated that iron-sulfur clusters had been successfully incorporated into f-HupS. This is further substantiated by the 420/315 nm absorbance ratio of 0.43, which is comparable with the corresponding ratio 0.68 found in ferredoxin II from Desulfovibrio gigas (29). In contrast, the often used 420/280 nm ratio is not a useful measure of purity due to the presence of NusA, 4 D. Camsund and P. Lindblad, personal communication.…”
Section: Resultsmentioning
confidence: 99%